Beyond the Ideal: Deconstructing Perfection in Aveus Har's ‘Istri Sempurna’ - Nurdiawan, Indra; Apriyani, Tristanti; Li, Hanyu (Universitas Ahmad Dahlan, 2025)
The standard of perfection illustrated in Istri Sempurna short story is embodied by a gynoid. However, this portrayal of perfection presents a dilemma in itself. This study focuses on the concept of an ideal life depicted in the short story Istri Sempurna. However, the existing literature review reveals a research gap, specifically that no research has discussed the value of perfection as portrayed in the short story Istri Sempurna through Derrida's perspective. The data collection technique in this study was carried out by reading and understanding the short story Istri Sempurna several times to obtain an overview of its themes and characters. This study attempts to apply Derrida's deconstruction principles, such as différance and binary opposition, to analyze how meanings in the text can shift and contradict each other. To ensure the validity and reliability of the study, data triangulation was carried out by comparing the results of the text analysis with relevant literature. The results of the study found that the concept of perfection depicted in Istri Sempurna short story is an ambiguity surrounding the idea of ​​perfection, which shows that what is considered ideal is not necessarily the same as true satisfaction or happiness. The findings of this study are expected to provide a new perspective on how the notion of perfection is constructed and deconstructed within contemporary Indonesian literature. Future research is recommended to explore similar themes using other poststructuralist approaches to enrich the discourse on gender, technology, and ideality in literary studies